Ecological space delineation and security analysis in the hilly areas of chongqing, China - Han, Wenyou; Lei, Jie; Wang, Wei; Gao, Runxia; Tian, Jinglian; Wang, Jinhong (Frontiers in Environmental Science, 2025)
The appropriate delineation of ecological space is crucial for ensuring ecological security, enhancing the regional environmental carrying capacity, and fostering sustainable economic and social development. For hilly and mountainous areas, there are few studies on ecological security pattern analysis combined with land use types. Taking Chongqing, China as a case study, this paper systematically developed an special evaluation system for ecosystem sensitivity (ES) and ecosystem service function (ESF) in hilly and mountainous areas, utilizing various sources of data from the year 2022 to support the delineation of ecological space types (EST), and analyzing ecological pattern security issues in conjunction with the current land use status. The results were as follows: (1) The ES was predominantly classified as extremely sensitive, comprising 47.54% (39,171.12 km2) of the area, characterized by high terrain and abundant forest resources, with a spatial trend of increasing from west to east. (2) The comprehensive ESF was primarily of general importance, accounting for 48.06% (39,603.89 km2), characterized by flat terrain and associated with areas of intensive development and construction, exhibiting a spatial trend of lower values in the northwest and higher values in the southeast. (3) Based on ES and ESF, we classified the EST into core, auxiliary, transitional, and development-friendly, representing 53.83% (44,360.12 km2), 9.15% (7,538.51 km2), 19.96% (16,450.80 km2), and 17.06% (14,052.57 km2), respectively, with 39.50% (13,574.00 km2) of the cultivated land located within the core-auxiliary ecological space, indicating a certain ecological security conflict. These findings lay the foundation for implementing scientifically effective management strategies in the study area, provide valuable insights for optimizing the national land use pattern in the hilly and mountainous areas of Southwest China, and assist management authorities in optimizing the spatial pattern of land.